Radiochemoimmunotherapy with intensity-modulated concomitant boost: interim analysis of the REACH trial - Jensen, Alexandra; Krauß, Jürgen; Potthoff, Karin; Simon, Christian; Nikoghosyan, Anna; Lossner, Karen; Debus, Jürgen; Münter, Marc (Radiation oncology, 2012)
To evaluate efficacy and toxicity clinical in the intensified treatment of locally advanced squamous cell carcinoma of the head and neck (SCCHN) with the combination of chemotherapy, the EGFR antibody cetuximab, and intensity-modulated radiation therapy (IMRT) in a concomitant boost concept.